Comparison Effect of Natural and Synthetic Superdisintigrants In Fast Dissolving Tablet Formulation - Sharma, Ranu; Kachhawa, Vijay; Alam, Junaid (Asian Journal of Pharmaceutical Research and Development, 2020)
The main object of the recent and present study is to develop the oral fast disintegrating tablets of levolfloxacin HCL using natural and synthetic disintegrants in order to find out the difference in drug release from the dosage form levofloxacin is an antibiotic which is used to treat number bacterial infection including , pneumonia ,urinary tract infections,chronicprostatitis and some type of gastroenteritis.we prepared levofloxacin HCL superdisintegranting tablet to treat bacterial infections.we studied the use of natural and synthetic disintrgrants in the preparation of levofloxacin tablet. The present study comprise all information of superdisintigrants including its type , mechanism ,selection criteria ,ideal properties incorporation method and advantage which are being used in the formulation to provide the safer ,effective drug delivary with patients compliance.